The Role of Kupang City Goverment in Law-Based Local Retribution Management - Aklis, Indah Aminah; Tanudjaja, Tanudjaja (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of Kupang City Government in the law-based management of local retribution. The method used is a mixed methods approach with a sequential explanatory design, which begins with a quantitative analysis of the contribution and effectiveness of user fees to local revenue (PAD), followed by a qualitative deepening through interviews and observations. The results show that the contribution of retribution to PAD is still relatively low (average <4%) and its effectiveness has not reached the minimum standard set by the government. The obstacles faced include the lack of technical regulations derived from the local regulation, limited use of digital system, weak supervision, and unoptimal tariff. Legally, retribution management has referred to the HKPD Law, but its implementation has not been supported by adequate technical instruments. This study recommends the reform of retribution governance through digitalization, regulatory reform, and institutional capacity strengthening to realize transparent and accountable local financial governance.Keywords: local retribution, local financial management, local goverment, Kupang City